A Deluxe Money Pump. (22nd December 2013) - Dougherty, Tom
<x xml:space="preserve">Abstract</x> So‐called money pump arguments aim to show that intransitive preferences are irrational because they will lead someone to accept a series of deals that leaves his/her financially worse off and better off in no respect. A common response to these arguments is the foresight response, which counters that the agent in question may see the exploitation coming, and refuse to trade at all. To obviate this response, I offer a "deluxe money pump argument" that applies dominance reasoning to a modified money pump case.